Air-Breakdown Triboelectric Nanogenerator Inspired by Transistor Architecture for Low-Force Human–Machine Interfaces - Munirathinam, Karthikeyan; Li, Longlong; Shanmugasundaram, Arunkumar; Park, Jongsung; Lee, Dong‑Weon (Nano-Micro Letters, 2026)
Human–machine interface (HMI) systems require energy harvesters that can operate efficiently under low contact forces, yet conventional tactile triboelectric nanogenerators (TENGs) suffer from low surface charge density and unstable output. Here, we propose a human skin electric field-induced air-breakdown TENG (AB-TENG) with a transistor-inspired architecture. The device employs a base terminal to collect electrons from human skin via an ionized air channel formed by air breakdown, enabling efficient conversion of the skin’s electric field through two operational modes: indirect (accumulated output) and direct (instant high output). In direct mode, the AB-TENG delivers 165 V at 2 N and 290 V at 24 N, with a peak power of 22 mW—22 times higher than conventional tactile TENGs. Practical utility is demonstrated through a self-powered infrared remote control and an ultrathin keyboard. This work establishes a new design paradigm that transforms air breakdown from a limitation into a functional mechanism, advancing skin-electricity-enhanced thin-film TENGs toward next-generation self-sustaining HMI platforms. Highlights: 1 An air-breakdown triboelectric nanogenerator (AB-TENG) is proposed with a transistor-inspired architecture to achieve high electrical output from the electrostatic discharge of skin electrons at a low contact force. 2 The working contact force of AB-TENG is compatible with the day-to-day human–machine interface systems, enabling the fabrication of next-generation thin electronics. 3 Demonstration of AB-TENG-based self-powered infrared remote control and an ultrathin self-powered keyboard with a thickness of 600 µm.